Effect of chemical interaction on the bonding strengths of self-etching adhesives to deproteinised dentine. Issue 8 (August 2015) - Zhou, Liqun; Wang, Yake; Yang, HongYe; Guo, Jinxin; Tay, Franklin R.; Huang, Cui
Abstract Objectives The present study examined (1) the chemical interaction between three self-etching adhesives and sodium hypochlorite (NaOCl)-deproteinised dentine, and (2) the influence of NaOCl treatment on bond strength of self-etching adhesives with/without adhesive functional monomers to dentine. Methods Caries-free dentine disks (control) and those treated with 5.25% NaOCl for 60 s were prepared. Xeno V (no functional monomers), G-Bond (containing 4-MET) or S3 Bond (containing 10-MDP) were applied to the NaOCl-treated dentine and either left without further treatment, or rinsed with 100% ethanol or distilled water. Attenuated total reflection (ATR) spectroscopy and field-emission scanning electron microscopy (FE-SEM) were used to evaluate the affinity of functional monomers with deproteinised dentine. Chemical interaction between the functional monomers and deproteinised dentine was evaluated using thin-film X-ray diffraction (TF-XRD). Microtensile bond strength (MTBS) was used to evaluate the mechanical property of the adhesives, either immediately or after thermo-cycling (5–55 °C) for 10, 000 cycles. Results According to the ATR and FE-SEM results, G-Bond and S3 Bond showed stronger affinity to deproteinised dentine than Xeno V even after rinsing with water. TF-XRD showed that chemical interaction between S3 Bond and deproteinised dentine occurred by formation of 10-MDP–Ca salt. Both deproteinisation and thermo-cycling adversely affected the MTBS of Xeno V (P < 0.05) but deproteinisation had no significant influence on S3 Bond. Conclusions When bonding to NaOCl-treated dentine, self-etch adhesives containing functional monomers (10-MDP) can maintain immediate and aged bond strengths after 10, 000 thermal cycles.